Optimized Dehydrogenation of Magnesium Hydride with Fe and Cu Additives - Gbenebor, Oluwashina; Popoola, Abimbola Patricia (Science, Engineering and Technology, 2024)
Solid state hydrogen storage with the use of MgH2 has gained widespread attention because of its good reversible storage capacity. This metal hydride however slowly releases hydrogen at high temperatures ranging between 325 – 375 oC. An important feature required of MgH2 is its ability to commence hydrogen release at a fast rate and reduced temperature. Transition metal-containing alloys/compounds having either Fe or Cu as the principal element have been used to improve the dissociation of hydrogen from MgH2.  Studies involving the use of each metal in its elemental form as an additive are minimal. This study investigated the catalytic effects of elemental Fe and Cu on the hydrogen release performance of MgH2 for potential applications in transportation and power generation. It was observed that MgH2/Fe had a better dehydrogenation performance; the temperature of onset of MgH2/Fe and MgH2/Cu dehydrogenation were 205, and 215 oC which were 98 and 88 oC lower than that for as-received MgH2.  The highest amount, 1.9 wt. % H2 was released by MgH2/Fe while 1.44 wt. % H2 was released by MgH2/Cu. The activation energy for dehydrogenation was reduced from 150.5 kJ/mol for as-received MgH2 to 89.8 and 79.8 kJ/mol in MgH2/Cu and MgH2/Fe respectively. It took 18.8 min for as-received MgH2 to commence dehydrogenation while that for MgH2/Fe and MgH2/Cu composites started from 12.2 and 13.4 min respectively. The in-situ formed Fe and Cu in MgH2 after milling acted as active catalytic sites for its improved dehydrogenation with MgH2/Fe behaving better.